Bark ringing in fruit crops - A review - Nithiya, S S; Saraswathy, S; Rajamanickam, C; Vijayasamundeeswari, A; Anitha, T (Plant Science Today, 2024)
Bark ringing or Girdling, a horticultural technique involving the removal of a strip of bark around the trunk or branches of fruit trees, has been widely studied and utilized to influence various aspects of fruit crop management. This practice primarily enhances fruit production, regulates canopy growth, and improves fruit quality. By interrupting the downward flow of nutrients and hormones, girdling can stimulate root development in hardwood cuttings and modify vegetative growth patterns. For instance, it has effectively reduced canopy shoot growth in vigorous apple cultivars, thereby improving fruit yield and quality. Additionally, girdling techniques such as notching and scoring control shoot growth and promote scaffold development in young trees. The method also has implications for nutrient distribution, as it can impact the formation of callus tissue and affect recovery processes. Despite its benefits, girdling can lead to undesirable outcomes, such as basal sprouting below the girdle. This abstract summarizes the critical applications, effects and considerations of girdling in fruit crop management, highlighting its role in optimizing fruit production and tree health.